ADVANCING CHILD RIGHTS IN URBAN GOVERNANCE: AN ANALYSIS OF POLICY IMPLEMENTATION AND CHALLENGES IN THE CHILD-FRIENDLY CITY INITIATIVE IN INDONESIA - Rofi Wahanisa; R. Benny Riyanto; Eko Mukminto; Syahwal Syahwal; Septhian Eka Adiyatma; Uche Nnawulezi (Masalah-Masalah Hukum, 2025)
The Child-Friendly City program in Indonesia aims to integrate children's rights into urban governance, promoting safe, inclusive environments for children’s development. Initiated by the Ministry of Women’s Empowerment and Child Protection, this program has expanded significantly since its inception in the 2010s. It has gained recognition for establishing child-friendly infrastructure and services such as playgrounds, libraries, and health centers. However, rapid urbanization and climate risks have posed new challenges, prompting the inclusion of children’s participation in urban decision-making. The program is guided by 24 indicators assessing health, education, protection, and participation, categorizing cities into four achievement levels. Despite successes, empirical data from Pemalang Regency reveals a gap between policy aspirations and outcomes, with rising child violence cases indicating ineffective child protection. The study explores the discrepancy between policy formulation and implementation, analyzing institutional barriers such as fragmented governance, inadequate coordination, and resource constraints. Additionally, socio-cultural factors, including the view of child protection as a familial responsibility, further hinder progress. This research employs a non-doctrinal approach, combining legal and field-based analysis to identify these challenges and offer recommendations. The findings emphasize the need for comprehensive data systems, enhanced child protection training, and stronger coordination among local actors. By incorporating children’s voices into policy creation and strengthening legal frameworks, the Child-Friendly City program in Pemalang can become a model for broader child-rights realization, ensuring children’s safety, participation, and well-being in urban governance.